2015
DOI: 10.1007/s10096-015-2493-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential characteristics of healthcare-associated compared to community-acquired febrile urinary tract infections in males

Abstract: The objective of this study was to analyse the characteristics of healthcare-associated febrile urinary tract infection (HCA-FUTI) compared to community-acquired FUTI (CA-FUTI) in men. An ambispective cross-sectional study in which we recorded clinical and microbiology data and outcomes from males with FUTI attended in the Emergency Department was carried out. A total of 479 males with FUTI, 162 (33.8%) HCA-FUTI and 317 (66.2%) CA-FUTI, were included. HCA-FUTI patients were older (p < 0.001), had higher Charls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
6
0
2
Order By: Relevance
“…Of the total of 31.9% of previous antibiotic users for UTI or other than UTI, 52% of them were culture-positive. Our studies reflected that the prior and continuous use of antibiotics correlates with the UTI because the widespread use of antibiotics may cause multiple drug resistance microorganisms, this finding correlated with the study conducted in India [ 50 ] and Bangladesh [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…Of the total of 31.9% of previous antibiotic users for UTI or other than UTI, 52% of them were culture-positive. Our studies reflected that the prior and continuous use of antibiotics correlates with the UTI because the widespread use of antibiotics may cause multiple drug resistance microorganisms, this finding correlated with the study conducted in India [ 50 ] and Bangladesh [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, patients with CO-HCA infections were older and had more underlying [13,14,17,18,35]. The rising rates of elderly and complex patients managed in the community setting could explain this fact.…”
Section: Discussionmentioning
confidence: 63%
“…CO-HCA infections involve a heterogeneous group of patients, such as long-term care facility patients, hemodialysis patients or outpatients receiving intravenous chemotherapy [12]. These infections occur in more complex patients and are associated with worse outcomes than community-acquired infections [13][14][15][16]. Nevertheless, little is known about whether CO-HCA infections behave differently from those acquired in the hospital setting [17].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the antibiotic use itself could increase the risk of MDR‐UTI, even if antibiotics had been used for diseases other than UTI. Some studies reported an association between MDR bacteriuria and previous antibiotic prescription among LTCF residents . As reported by previous studies, LTCF residents were at a high risk of infection with MDR pathogens …”
Section: Discussionmentioning
confidence: 71%
“…Some studies reported an association between MDR bacteriuria and previous antibiotic prescription among LTCF residents. [12][13][14] As reported by previous studies, LTCF residents were at a high risk of infection with MDR pathogens. 10,12,[15][16][17][18] In the present study, a certified care level ≥1 was one of the risk factors for MDR bacteriuria in univariate analysis.…”
Section: Escherichia Colimentioning
confidence: 66%